2010
DOI: 10.1139/w10-010
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliserogroup O2 and O28ac O-antigen gene cluster sequences and detection of pathogenicE. coliO2 and O28ac by PCR

Abstract: The O-antigen gene clusters of Escherichia coli serogroups O2 and O28ac were sequenced, and PCR assays were developed to identify strains belonging to these 2 serogroups. Sixteen and 8 open reading frames were mapped to these loci in E. coli O2:H4 U 9-41 and E. coli O28ac:H25 96-3286, respectively. The wzx (O-antigen flippase) and wzy (O-antigen polymerase) genes in the E. coli O2 and O28ac O-antigen gene clusters were selected as targets for PCR assays for their identification. PCR assays targeting the wzx an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The O serotype of each isolate was confirmed by agglutination using a single E. coli O-serotypespecific antiserum (Statens Serum Institut, Denmark) and PCR using O-serotype-specific primers described by Fratamico et al (32) and Li et al (33). Assay working stocks were created on the basis of the method described by Burton and Nahm (34).…”
Section: Discussionmentioning
confidence: 99%
“…The O serotype of each isolate was confirmed by agglutination using a single E. coli O-serotypespecific antiserum (Statens Serum Institut, Denmark) and PCR using O-serotype-specific primers described by Fratamico et al (32) and Li et al (33). Assay working stocks were created on the basis of the method described by Burton and Nahm (34).…”
Section: Discussionmentioning
confidence: 99%
“…Since our results showed that antibiotic treatment markedly induced translocation of members of the Enterobacteriaceae to MLNs, the translocation of injected pathogenic K. pneumoniae organisms and the nonvirulent E. coli strain DH10B/DsRed was used to investigate the effect of intestinal microflora depletion on intestinal immunity. The E. coli strain DH10B without the virulence plasmid and with a plasmid carrying the dsRED2 gene fragment was used to generate the nonvirulent DH10B/DsRed strain (25). After antibiotic treatment for 6 days, there was a marked increase in the translocation of pathogenic K. pneumoniae to MLNs, liver, and blood (93-fold, 23-fold, and 41-fold, respectively) but not that of DH10B/DsRed.…”
Section: Discussionmentioning
confidence: 99%
“…There are 7 genes in this operon, including beta-carotene hydroxylase (crtZ), phytoene synthase (crtB), phytoene dehydrogenase Cronobacter O-antigen gene cluster. Another potential strainor serogroup-specific gene cluster, the O-antigen gene cluster, was investigated to determine its suitability as a biomarker (15,16,38,41). The O-antigen gene cluster contains genes with distinctly different functions, including genes involved in the processing and assembly of the O antigen.…”
Section: Resultsmentioning
confidence: 99%
“…The O-antigen gene cluster contains genes with distinctly different functions, including genes involved in the processing and assembly of the O antigen. The genes that encode the O antigen flippase (wzx) and the O antigen polymerase (wzy) are extensively used as biomarker genes for Salmonella and E. coli serotyping (15,16) and may be suitable biomarkers for Cronobacter spp. as well (Table 4).…”
Section: Resultsmentioning
confidence: 99%